THE HISTORY OF TRANSLATION AND THE CURRENT STATUS OF TRANSLATOR – INTERPRETER TRAINING IN JAPAN - Thi Nga My, Dao (VNU Journal of Foreign Studies, 2022)
The teaching of translation – interpretation in Japan has different characteristics compared to the West and neighbouring countries. A study into the current status of translation and interpretation teaching in Japan and its existing problems will provide suggestions for training in translation and interpretation in Vietnam. Simultaneously, this article also summarizes previous Japanese researches on the reality of teaching and learning translation and interpretation at Japanese universities. It is hoped that specific information about lecturers, class size, existing problems and learners’ aspirations will be constructive to the development of translation and interpretation at Vietnamese universities.